FACTORS AFFECTING INDONESIAN STUDENTS’ WILLINGNESS TO COMMUNICATE (A CASE STUDY IN HIGHER EDUCATION) - Hesti Wijaya; Putri Amalia Rizkina (University of Muhammadiyah Purwokerto, 2015)
The push toward language teaching to make learners effective communicators has been relentless. To be proficient language users, learners need to at least practice it inside the classroom to communicate functionally and interactively. Through such a way, they will be accustomed to the language not only from linguistic and structural matters, but also from authentic communicative competence. Willingness to Communicate (WTC), hence, is a crucial plus point for learners to succeed their L2 acquisition. This present study which was held in EFL context aimed to: (1) examine the Indonesian students’ level of WTC in English, and (2) reveal the potential factors which influence students’ WTC in English. A total 136 undergraduate students from three different majors (Medicine, Accounting, Elementary School Teacher Education) participated in this study. The data were gathered through a survey and a semi-structured interview. It was indicated that 197 out of 136 students (72.1%) had low Willingness to Communicate in English. Besides, it was disclosed that there were four most discouraging factors affecting students’ WTC, namely language anxiety, task-type, teachers’ and students’ rapport, and class size. Keywords: Willingness to Communicate (WTC), Indonesian students, EFL context